Medial thigh lift in post-bariatric patients: Our encouraging experience. Issue 6 (1st November 2016) - Simone, Pierfranco; Carusi, Carlo; Del Buono, Romualdo; Persichetti, Paolo
Abstract: Background: A high rate of postoperative complications following inner thigh lift is reported in the medical literature. The authors present the results of a study on the validity of inner thigh contouring, with liposuction and concomitant skin excision, in postbariatric patients. Methods: This study examined the charts of 46 postbariatric female patients, who underwent medial thigh lift with a 'T' scar technique and concomitant liposuction, between February 2010 and February 2013. Complications were recorded. A questionnaire was administered to the patients at the 1-year follow-up visit. Preoperative and 1-year postoperative photographs were compared, superimposed, and analysed. Results: This study did not observe major systemic complications, haematoma, seroma, infection, skin necrosis, lymphoceles, or lymphoedema. Minor complications were three cases of wound dehiscence and two cases of deepithelialisation. At the 1-year follow-up visit, caudal scar migration, genital distortion, recurrent ptosis, or deformity of the inner thigh contour were not observed. Questionnaires and a comparison of pre- and 1-year postoperative pictures showed encouraging results. Conclusions: The medial thigh lift technique described and assessed in this article is a straightforward surgical procedure, with considerable functional and aesthetic results. Liposuction, early mobilisation, and appropriate postoperative management are pivotal to reduce postoperative downtime and complications.